2022
DOI: 10.3390/nu14122432
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Suppresses Cognitive Decline of HFD-Induced Obese Mice through Reversing Hippocampal Inflammation, Insulin Resistance, and BDNF Level

Abstract: Obesity is an important public health problem nowadays. Long-term obesity can trigger a series of chronic diseases and impair the learning and memory function of the brain. Current studies show that scientific exercise can effectively improve learning and memory capacity, which also can provide benefits for obese people. However, the underlying mechanisms for the improvement of cognitive capacity under the status of obesity still need to be further explored. In the present study, the obesity-induced cognition-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Recent studies have highlighted the correlation between excessive consumption of HFDs and elevated Moreover, studies have reported that obese mice subjected to long-term HFDs are prone to cognitive recognition and social impairments [37,39,53]. Consistent with these ndings, we observed that propionate treatment signi cantly impaired mice's ability to recognize novel objects, resulting in a notable disparity in exploration time between old and new objects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent studies have highlighted the correlation between excessive consumption of HFDs and elevated Moreover, studies have reported that obese mice subjected to long-term HFDs are prone to cognitive recognition and social impairments [37,39,53]. Consistent with these ndings, we observed that propionate treatment signi cantly impaired mice's ability to recognize novel objects, resulting in a notable disparity in exploration time between old and new objects.…”
Section: Discussionsupporting
confidence: 87%
“…Typically, learning and memory functions undergo rapid development during adolescence [37], while longterm consumption of high-fat diets exerts adverse effects on the brain and nervous system [38]. Thus, we employed the NORT to evaluate alterations in learning and memory abilities in HFD mice (Fig.…”
Section: Propionate Exacerbates Cognitive Social Behavior Disorder In...mentioning
confidence: 99%
“…Obesity also becomes the hotbed and triggers multiple diseases. Relevant studies have shown that RSV can prevent diet-induced obesity and insulin resistance by activating SIRT1 and PGC-1α to improve mitochondrial oxidative phosphorylation function [113][114] . RSV also can reduce the accumulation of fat in obesity by inhibiting mitochondrial biogenesis, inducing preadipocyte differentiation [115] , and alleviating insulin resistance by increasing mitochondrial activity in brown adipose tissue [116] .…”
Section: Rsv Raises Mitochondrial Function For the Prevention And Tre...mentioning
confidence: 99%
“…EEG data exhibited a notable reduction in N2 amplitudes and a decline in theta power when exposed to high-calorie foods, which serves as an indicator of cognitive impairments. The study by H. Zhang et al investigated cognitive decline in obese mice, highlighting the beneficial effects of swimming [ 14 ]. Obesity led to cognitive impairment, but an 8-week swimming regimen mitigated this decline by reducing inflammation, inhibiting the JNK/IRS-1/PI3K/Akt pathway, and activating the PGC-1α/BDNF pathway.…”
Section: Neurological and Cognitive Functionmentioning
confidence: 99%